Revolutionizing EFL special education: how ChatGPT is transforming the way teachers approach language learning - Mogbel Aid K. Alenezi; Amr M. Mohamed; Tahany S. Shaaban (Universidad de Málaga, 2023)
This mixed-methods study explored the attitudes of 199 English as a Foreign Language (EFL) special education teachers towards using ChatGPT for language learning. The survey questionnaire, consisting of 21 items, examined attitudes, effectiveness, barriers, and the future use of ChatGPT. The results revealed that participants held moderate attitudes, perceiving ChatGPT as moderately effective with moderate barriers. While no significant differences were found between male and female teachers in attitudes and effectiveness, significant gender differences emerged in the future use of ChatGPT, with female teachers exhibiting a greater willingness to embrace it. Follow-up email interviews with five participants provided valuable insights into strategies, effectiveness, challenges, and inclusivity when using ChatGPT in language instruction for special education students. These findings contribute to implementing and developing ChatGPT as a language learning tool for EFL special education students, emphasizing the importance of gender-inclusive approaches and practical considerations to enhance its efficacy.